PENGARUH PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM TERHADAP PERILAKU KEAGAMAAN SISWA KELAS VII dan VIII SMP 17 AGUSTUS 1945 TEGALDLIMO - Ahmad Fanani (INCARE, International Journal of Educational Resources, 2020)
The study was conducted in grades VII and VIII of SMP 17 August 1945 Tegaldlimo. This type of research uses quantitative research. With the title Effect of Learning Achievement in Islamic Education Against Religious Behavior of Class VII and VIII Middle School Students August 17, 1945 Tegaldlimo. This study aims to determine the effect of Islamic Religious Education learning achievement on religious behavior of VII and VIII grade students on 17 August 1945 Middle School Tegaldlimo. The population of this research is VII and VIII grade students of SMP 17 August 1945 Tegaldlimo with a total of 48 students. The research sample was taken 100%. The data analysis technique uses the Product Moment Devised formula using SPSS 16.0 for Windows. The results showed that there was a proven influence on Islamic religious education learning achievement on the religious behavior of Grade VII and VIII students of SMP 17 August 1945 Tegaldlimo with a correlation magnitude of 0.580, located at 0.410 - 0.600, which means a moderate correlation level. While the magnitude of the coefficient of learning achievement of Islamic Religious Education on religious behavior of VII and VIII students of SMP 17 August 1945 was 0.580 with a Significant level of 5% = 0.291 which means that r count is greater than r table means Ha is accepted and Ho is rejected.